The Performance of Multiple Imputation in Social Surveys with Missing Data from Planned Missingness and Item Nonresponse - Julian B. Axenfeld; Christian Bruch; Christof Wolf; Annelies G. Blom (Survey Research Methods)
Designs using planned missingness, such as the split questionnaire design, are becoming more and more important in social survey research. To ensure an acceptable questionnaire length, these approaches typically entail large amounts of planned missing data, which can be imputed after data collection. However, social surveys typically also include other types of missingness such as item nonresponse by survey participants, which need to be imputed as well. This entails a complex imputation task with amounts of missing data larger than initially planned and a potentially non-random, heterogeneous mechanism. Yet, it remains to be studied whether accurate multiple-imputation estimates can be obtained in practice with planned missingness and item nonresponse.